Pengaruh Kompensasi, Disiplin Kerja, dan Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan Biro Umum Pengadaan Sekretariat Jenderal Kementerian Pertanian RI - Amelia Agustina, Nanda; Siska, Elmira; Indra, Natal (Universitas 17 Agustus 1945 Semarang, 2025)
This study focuses on determining the effect of compensation, work discipline, work environment on the work productivity of employees of Biro Umum Pengadaan in Sekretariat Jenderal of the Republic of Indonesia using quantitative approaches. The sampling technique uses simple random sampling and the number of samples obtained by 53 respondents using questionnaires. In data processing using SPSS 26.0 software data instrument tests, multiple linear regression analysis, and hypothesis tests. Based on the results of simultaneous research, it was found that compensation, work discipline and work environment have a positife and significant effect on work productivity of employees of Biro Umum Pengadaan in Sekretariat Jenderal of the Republic of Indonesia.